Management of patients with pulmonary arterial hypertension against of systemic sclerodermia (part 1). - Yehudina, Ye. D.; Kalashnykova, O. S. (Medicni Perspektivi, 2018)
Pulmonary arterial hypertension (PAH) is a serious condition caused by the damage to the small pulmonary vessels, leading to the increase of pulmonary artery pressure, pulmonary vascular resistance, development of right ventricular failure and death. PAH is one of the actual problems of modern medicine due to low survival rate, rapid disability of the patients and a high cost of treatment. PAH is one of the leading causes of death in systemic scleroderma (SSD). PAH associated with scleroderma is a unique phenotype combining the manifestations of both SSD and PAH, the pathogenetic mechanisms of which modify the clinical picture and the course of these conditions. Timely diagnosis and treatment of PAH show significant effect on survival rates, however, early detection of PAH is still difficult in SSD due to several factors. The main causes are restriction of modern screening methods and polyorganic involvement in SSD. In comparison with other subgroups of PAH the patients with SSD-PAH poorly answer to the specific PAH therapy. SSD-PAH, along with idiopathic pulmonary hypertension (IPAH), belongs to group I of pulmonary hypertension classification and according to modern consensus has a similar pathogenesis and clinical picture, however, differences in the response to therapy in these groups are observed, that indicates the role of other pathobiological mechanisms. Recent investigations explain these differences by such factors as autoimmune and inflammatory responses, more severe vascular remodeling and direct myocardial damage in the SSD. Drug therapy of PH in SSD is similar to that in IPAH and includes prostaglandins, endothelin receptor antagonists, calcium channel blockers, which are prescribed in cases of a positive vasoreactive test, PDE-5 inhibitors. In this literature review we showed traditional and new methods of PAH treatment and their relevance to SSD-PAH in accordance with randomized clinical trials.